Perancangan Koordinasi Proteksi Di Pt PertaminaEp-Central Processing Plant Area Gundih - Ariyanta, Riki; , Aris Budiman, S.T., M.T (2017)
Damages on the electrical loads and distribution equipments often occur due to disturbances. Disorders can be result from internal or external factors. One disorders that often occurs is short circuit. Isolating the fault need arotection equipment, namely overcurrent relay. In the application, to get well protection coordination, mutual current and time setting is needed between relays. Electrical Power tribution System of PT Pertamina EP-Central Processing Plant Area Gundih uses fuses those must be replaced after used. The protection devices have not ben coordinated yet. The research about designing coordination protection in PT Pertamina EP-Central Processing Plant Gundih Area is needed. This research starts with gathering data the electrical needed. Then using ETAP Power Station 12.6 application to make the single line diagram. The next step is calculating the value of short circuit current on the closest bus from relay, which already been placed. After that is do the setting overcurrent relay using all the data that has been gathered. The last step is the depiction of overcurrent relay coordination's curve and analysis. The results shows the magnitude of the short circuit current, the layout of the relay, stages of coordination and other parameters that are used to determine the overcurrent relay settings. The closer the location of the relay from the load, the current and time setting must be smaller than the relay setting behind itKeywords: overcurrent relay, protectioncoordination ETAP 12.6.